Analisis Dompet Digital “Link Aja Syariah” dari Perspektif Maslahah Mursalah - Anisa Fadilah Zustika; Achmad Fageh (University of Darussalam Gontor, 2022)
Industry of 4.0 era it is no stranger to talk about digital wallets whose existence can make it easier for humans to make payment systems.There are many kinds of digital wallets in Indonesia, first one that is sharia-based is the